(3GdLed hGdYbhOs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Mb MeOg (B... (3aCfG eLjH Edi eSGFd GdTjN (B.. (3ef EedGA eNJUQ jTJed Ydi PcQ cJH GdYHGOGJ hPcQ YbhO CHhGHgG hMUQ LedgG hHjGf CaYGdgGs
(3BNQgG (B:s
(3BNQgG(B: (3hGeKdI Pdc HjfGgG aj GdfgGjI agPg Led bO dNUfGgG hYbOfGgG aj cd cJGH Ydi ZGjI LgOfG hWGbJfG hfQLh Cf jchf GdGfJaGY def jfYe GdfXQ ajgG hGf jLYdg Gddg JHGQc hJYGdi dhLgg NGdUGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 84s
(3GdPQjYI, L (B5: 103s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis